Gangguan Makan dan Stres Berkorelasi Positif dengan Indeks Massa Tubuh Remaja di Sekolah Menengah Pertama Attaqwa 02 Tarumajaya - Rinova, Rinova Aprillia Utari; Angkasa, Dudung; Wahyuni, Yulia; Kuswari, Mury; Harna (Media Gizi Kesmas, 2024)
Background: Poor body perceptions may cause stress that leads to an increased risk of eating disorders that subsequently affect nutritional status. However, this relationship in adolescents is still hardly explored. Objectives: To examine the relationship between eating disorders, body perception, stress scores, and body mass index in adolescents. Methods: This cross-sectional study involved 33 teenagers aged 13-16 years at Attaqwa 02 Tarumajaya Middle School who were drawn using stratified random sampling. Eating disorders, body perception, and stress score were assessed by the Eating Atittude Test-40, Multidimensional Body-Self Relations Questioner Appearance Scale, and a modified Depression Anxiety Stress Scale-42, respectively. Body mass index for age z-score (BAZ) was generated from anthropometric measurements. Relationships were tested by Pearson and Partial correlations. Results: More than half of the respondents were boys (51.5%). Eating disorders (r= 0.399) and stress scores (r= 0.539) were significantly and positively associated with BAZ in adolescents. The relationship remains significant although a bit attenuated after adjusted by age (r= 0.375; r= 0.562) and gender (r= 0.388; r= 0.516). No association was found between body perception and BAZ (r= -0.027). After adjusting by age (r= -0.107) and gender (r= -0.052) the association remained insignificant. Conclusions: Eating disorders and stress scores correlated significantly with body mass index z-score in adolescents. Health and nutrition promotion to prevent eating disorders and stress should be encouraged to reduce the risk of obesity in adolescents.